Impact of Fungicide Application and Late Blight Development on Potato Growth Parameters and Yield in the Tropical Highlands of Kenya and Uganda - Ojiambo, P. S.; Namanda, S.; Olanya, O. M.; El-Bedewy, R.; Hakiza, J. J.; Adipala, E.; Forbes, G. (African Crop Science Journal, 2001)
The effects of fungicide application and late blight development on potato varieties with different levels of resistance to late blight were quantified in Kenya and Uganda during the 1999 cropping seasons. Experiments were laid out in a randomised complete block design with three replications in three sites, Loreto and Kabete in Kenya and Kalengyere Research Station in Uganda. At each experimental site, plots consisted of 4 m rows with plants spaced at 0.75m x 0.3 m. Treatments consisted of three potato varieties and four application intervals of Dithane M-45 arranged in a factorial combination. Areas under disease progress curves (AUDPCs) was significantly lower in the sprayed plots than in the unsprayed plots. Disease levels were lower in plots with 7 days application interval and most severe in plots of 21 days spray interval. Yields were higher in the 7 days intervals and lower in the 14, 21-days intervals and in the unsprayed plots. Fresh tuber weights and dry tuber weights were higher in the sprayed plots and lower in the unsprayed plots, respectively. At Kabete, Kerr's Pink had the highest AUDPC value of 2139.3 and disease was least on Asante with an AUDPC value of 409.4. The corresponding AUDPC values for the control plots were 671.5, 945.6 and 2367.8 for Asante, Tigoni and Kerr's Pink, respectively. At Loreto, disease was also most severe on Kerr's Pink with an AUDPC value of 2076.3 and least severe on Tigoni that had an AUDPC value of 444.8. The corresponding AUDPC values for the control plots were 840.4, 1000.2 and 2740.0, for Tigoni, Asante and Kerr's Pink, respectively. The highest tuber yield of 41.3 t ha-1 recorded at Kabete for Asante was significantly higher than yields of Kerr's Pink (22.0 t ha-1) but was not different from the yields of Tigoni (39.9 t ha-1). At Loreto, Tigoni had the highest yields of 34.6 t ha-1 that was significantly different from that of Kerr's Pink (6.2 t ha-1) in the sprayed plots. At Kalengyere, disease levels were significantly (P = 0.05) lower in the sprayed plots than in the control plots and disease severity was least on variety Rutuku (AUDPC value of 17.9) in 7 day spray interval. Tuber yields were significantly (P = 0.05) higher in the sprayed plots and highest tuber yield was recorded on variety Kabale (39.5 t ha-1) in plots with 7 day spraying interval.
Keywords: yield; fungicide; late blight; growth parameters; general resistance